Index of Religious Moderation among Students of Madrasah Aliyah Negeri 1 Jembrana - Wiguna, I Made Arsa; Perbowosari, Heny; Subagya, Agus; Asror, Chozinatul; Harikrishnan, Harikrishnan (Analisa: Journal of Social Science and Religion, 2024)
This research aims to measure how high or low the religious moderation index is for students at Madrasah Aliyah Negeri (MAN) 1 Jembrana. Research on religious moderation, that measures the index of religious Moderation, especially in Madrasah students, has not been carried out, so this research is expected to contribute to the adoption of policies related to the implementation of religious moderation in educational institutions. The method used in this study was a survey of 285 samples using probability sampling and a closed questionnaire covering 30 positive and 5 negative statements by deducting from each indicator of religious moderation namely national commitment, tolerance, anti-violence, and adaptation to local culture. The findings are generally, the Religious Moderation Index of Students MAN 1 Jembrana is at a very high level (3.45). If viewed from its four indicators, then the National Commitment Index is at 3.10 or High category. The Tolerance Index was at 3.46 including very high category. However, based on research findings, it is necessary to strengthen several aspects for students, including adherence to nationalism, respect for other religious beliefs and local culture, prevention of intolerance and radicalism, and the right meaning of jihad.